Recruitment, Retention and Compliance of Overweight Inactive Adults with Intermediate Hyperglycaemia to a Novel Walking Intervention - Faulkner, Maria; McNeilly, Andrea; Davison, Gareth; Rowe, David; Hewitt, Allan; Nevill, Alan; Duly, Ellie; Trinick, Tom; Murphy, Marie (Obesities, 2021)
This study evaluated the effectiveness of strategies used to recruit and retain overweight, inactive adults with intermediate hyperglycaemia (IHG) to a novel walking programme. Participant compliance to the nine-month randomised controlled trial (RCT) is also presented. Inactive overweight (BMI ≥ 25 kg/m2) adults (N = 42; n = 19 male, n = 23 female) aged between 18–65 years, with IHG were identified via three recruitment strategies (NHS database reviews, diabetic clinics, and a University population). Participants were randomly assigned to either Intervention Group (IG n = 22; n = 11 male, n = 11 female) or Usual Care (UC n = 20; n = 8 male, n = 12 female). IG followed a nine-month novel behaviour change intervention where they walked in accordance with physical activity guidelines using the beat of music to maintain appropriate cadence. UC received standard physical activity advice. Recruitment, retention, and intervention compliance were calculated using descriptive statistics (means or frequencies). Recruiting from a University population was the most successful strategy (64.2% response rate) followed by NHS database reviews (35.8%) and then diabetic clinics (0%). Study retention was ≥80% in both groups throughout the RCT. Intervention compliance was highest from baseline to four months (70.1 ± 39.2%) and decreased as the study progressed (43.4 ± 56.1% at four to six months and 37.5 ± 43.5% at follow-up). In total, 71.4% of IG walking completed throughout the study was at least moderate intensity. A novel walking intervention incorporating the use of music along with behaviour change techniques appears to positively influence the recruitment, retention, and walking compliance of this population.